ANALYSIS OF DIFFERENT TECHNIQUES FOR IMPROVING PERFORMANCE OF FLAT PLATE SOLAR COLLECTORS FOR FRUITS DRYING - Bakari, Ramadhani; Minja, Rwaichi; Njau, Karoli (Tanzania Journal of Engineering and Technology, 2017)
Fruits drying had become a broader technology in fruits and vegetables value addition. The technology is reported to be a promising way of drying without incurring higher cost but its adaptation has not been feasible in rural areas. Solar dryers have been developed but its poor performance limits its applicability. In this study, several techniques for modifications of traditional solar collector were addressed. It was observed that, varying collector designs in different techniques, a range of collector performances can be archived. The research shows that, collector efficiency can be improved by 9.6% when employing double duct counter flow compared to conventional collectors. Likewise, performance difference between conventional collectors and studied models were found to be 8%, 7.2%, 6.1% and 5.2% for model parked with charcoal, 5 mm wire mesh, 4 mm glass thickness and 8 baffles respectively. This study shows that, double duct counter flow system is the best option for improving the performance of the collectors, followed by charcoal and wire mesh. On the hand, using 4 mm glass thickness gave improved performance, however, it is recommended for collector size not exceeding 2 m in length.